Spontaneous Coronary Dissection: “Live Flash” Optical Coherence Tomography Guided Angioplasty - Angela Pimenta Bento; Renato Gil dos Santos Pinto Fernandes; David Cintra Henriques Silva Neves; Lino Manuel Ribeiro Patrício; José Eduardo Chambel de Aguiar (Case Reports in Cardiology)
Optical Coherence tomography (OCT) is a light-based imaging modality which shows tremendous potential in the setting of coronary imaging. Spontaneous coronary artery dissection (SCAD) is an infrequent cause of acute coronary syndrome (ACS). The diagnosis of SCAD is made mainly with invasive coronary angiography, although adjunctive imaging modalities such as computed tomography angiography, IVUS, and OCT may increase the diagnostic yield. The authors describe a clinical case of a young woman admitted with the diagnosis of ACS. The ACS was caused by SCAD detected in the coronary angiography and the angioplasty was guided by OCT. OCT use in the setting of SCAD has been already described and the true innovation in this case was this unique use of OCT. The guidance of angioplasty with live and short images was very useful as it allowed clearly identifying the position of the guidewires at any given moment without the use of prohibitive amounts of contrast.